2012
DOI: 10.1002/ange.201108639
|View full text |Cite
|
Sign up to set email alerts
|

C‐H‐Funktionalisierung durch eine intramolekulare Redox‐Strategie

Abstract: Teamarbeit: Eine Eintopfmethode zur α-Funktionalisierung von Aminen unter paralleler Reduktion einer Nachbargruppe wurde entwickelt. Die Methode nutzt einen intramolekularen Redoxprozess und vermeidet so den Einsatz zusätzlicher Oxidationsmittel. Der präparative Nutzen wurde anhand der kurzen, fünfstufigen Synthese von Indolizidin-167B demonstriert

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 47 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…Secondly, to date, there has been no experimental evidence or theoretical investigation regarding the proton-transfer pathway or its stereochemical features in a catalyzed process. [9] In addition, it remains unclear how a rate-limiting 1,5-H transfer dictates the subsequent stereochemistry-generating C À X bond-formation step. Herein, we report our detailed computational investigations, as well as experimental studies, with the aim of addressing these mechanistic puzzles.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, to date, there has been no experimental evidence or theoretical investigation regarding the proton-transfer pathway or its stereochemical features in a catalyzed process. [9] In addition, it remains unclear how a rate-limiting 1,5-H transfer dictates the subsequent stereochemistry-generating C À X bond-formation step. Herein, we report our detailed computational investigations, as well as experimental studies, with the aim of addressing these mechanistic puzzles.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, this process involves a [1,5]-hydride shift, catalyzed by Lewis or Brønsted acids, which have attracted much attention lately. [9] Herein, we would like to report on the synthesis of geometrically pure allylic b,b-dichloroamines by using a Lewis acid promoted reaction between a,a-dichloroaldimines and terminal alkynes. The reaction mechanism and feasibility of the vinylation process was supported by quantum mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[16] More recently we also showed that the generation of vinamidinium intermediates [17] arising from 1,3-propanediols and amines led to various julolidines through an electrocyclization/b-alkylation sequence. [18] Herein we disclose the applicationo fo ur catalytic systems with the use of 2-hydroxybenzaldehyde derivatives and cyclic tertiary amines to afford straightforward access to the corresponding functionalized cyclic hemiaminal ethers [19] by vicinal a,b-difunctionalization. The unprecedented formationo fa-alkylatedl actamsf rom the starting tertiaryc yclic amines is also successfully achieved by af ormal endo-cyclic dehydrogenative hydrolysis involving the iminium intermediates ( Figure 1).…”
mentioning
confidence: 99%